Effect of hardness gradient of laser bionic coupling unit on wear resistance of 6082 aluminum alloy. (September 2022) - Zhao, Guoping; Yuan, Yuhuan; Zhang, Peng; Zhou, Ti; Wang, Haowei; Li, Xianfeng; Zhou, Hong
Highlights: Bionic surfaces with various units hardness gradients were prepared by laser on 6082 Al alloy to imitate non-smooth surface of shells. The units presented superior microstructure and hardness. The wear resistance of Al alloy was increased by 72.57%. The optimal unit hardness gradient distribution for wear resistance was obtained. The wear resistance mechanism was deeply analyzed. Abstract: Different hardness units were processed by laser melting according to the study and observation of wear-resistant surfaces of shells. Then a biomimetic 6082 aluminum alloy surface consisting of various hardness gradient units was formed to simulate the non-smooth surface of natural organisms. The influence of unit hardness gradient on wear resistance was discussed. Wear test showed the bionic units positively affected the wear resistance of samples. Experiment showed the wear resistance of bionic samples with units of three hardness gradients was the highest. At the same time, The bionic wear-resistant mechanism of "soft and hard phases" was deeply analyzed and discussed.